Exploring the Impact of Extroversion and Introversion Personality Types on EFL Learners’ Preferences in Publishing Research Papers - Ikrar Genidal Riadil; Muhammad Rauuf Oktavian Nur (IJELR: International Journal of Education, Language, and Religion, 2020)
Personality may affect our way to learn. Based on the essential role of various forms of personalities in the cycle of studying foreign languages and understanding foreign languages, this thesis seeks to explore the effect of extroversion and introversion on the identity of English as a foreign language learner in writing research articles. Fifty students are taking part in this study. Those participants are the fifth-semester students of Tidar University who take Teaching English as Foreign Language class. They have many papers from any lecture. They can produce more than three research papers in a year. Publishing their papers still become interesting topics for them. The researcher uses descriptive qualitative method to get the result. By giving a questionnaire to all of the participants to find out their personality types and then asking about their preferences in publishing research papers. Based on the findings, researcher get main result, there are more extroverts EFL Learners than the introvert one. They could give wide perspectives about publishing their papers. Their perspectives on their preferences depend on any reason that supports the result.